The Efforts of the Al-Misbah Islamic Boarding School in Tasikmalaya City in Growing Adolescent Self Control (Santri) - Rifyal Luthfi MR; Nurhasanah; Oneng Maemunah; Dede Aji Mardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The background of the problem in this study, the researcher sees the reality of life in this day and age, there are many events and problems that are very worrying for the country. We often see news on television and from other information media which provide information that there have been several violations committed by teenagers. These various actions can occur because of a person's inability to control himself. Based on the background of the problem, the formulation of the problem which is the aim of the research is to find out the efforts of the Al-Misbah Islamic boarding school in Tasikmalaya City in fostering adolescent self-control and the impact on the Al-Misbah Islamic boarding school in Tasikmalaya City from efforts to foster adolescent self-control. The method used in this study is using qualitative methods. The type of research used by researchers is ethnography, which means in-depth research on behavior that occurs in a particular social or cultural group. Data collection techniques were carried out by researchers using two methods, namely observation and interviews. The results showed that the efforts of the Al-Misbah Islamic Boarding School in Tasikmalaya City to foster self-control in adolescents through peventive and persuasive efforts were the development of the Al-Misbah Islamic boarding school in Tasikmalaya City every year. has increased very well, such as the equality between the level of education at the Al-Misbah Islamic boarding school in Tasikmalaya City and the level of education at school, for example the Tsanawi level is equivalent to junior high school and Aliyah is equivalent to high school, besides that the three main programs of the curriculum have been set by the pondok pesantren institution can be achieved properly, while the three programs are ulama'ul amilin, imamul mutaqin and mutaqin.